1997
DOI: 10.1002/chin.199723031
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Conformations and Relative Stabilities of the cis and trans Isomers in a Series of Isolated N‐Phenylamides

Abstract: structure structure (organic substances) K 9000 -031Conformations and Relative Stabilities of the cis and trans Isomers in a Series of Isolated N-Phenylamides -(reinvestigation of the isomer distribution and conformational preference of formanilide acetanilide and N-methylformanilide; ab initio Hartree-Fock calculations). -(MANEA, V. P.; WILSON, K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 1 publication
5
14
0
Order By: Relevance
“…56 The observed c-FA/t-FA abundance ratios have been rationalized by experimental estimates of their energy difference ranging from ΔD 0 trans−cis = 276 ± 84 58 to 350 ± 150 56 and ∼875 cm −1 . 61 These values are in accordance with the theoretical predictions. 54,56,61,62,68 Isomer-selective IR spectra of t-/c-FA recorded in the hydride stretch (amide A, ν NH , ν CH ) and fingerprint (amide I−II) ranges demonstrate the large structural differences of the amide groups in the two isomers.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…56 The observed c-FA/t-FA abundance ratios have been rationalized by experimental estimates of their energy difference ranging from ΔD 0 trans−cis = 276 ± 84 58 to 350 ± 150 56 and ∼875 cm −1 . 61 These values are in accordance with the theoretical predictions. 54,56,61,62,68 Isomer-selective IR spectra of t-/c-FA recorded in the hydride stretch (amide A, ν NH , ν CH ) and fingerprint (amide I−II) ranges demonstrate the large structural differences of the amide groups in the two isomers.…”
Section: Introductionsupporting
confidence: 91%
“…61 These values are in accordance with the theoretical predictions. 54,56,61,62,68 Isomer-selective IR spectra of t-/c-FA recorded in the hydride stretch (amide A, ν NH , ν CH ) and fingerprint (amide I−II) ranges demonstrate the large structural differences of the amide groups in the two isomers. 59,60 Interestingly, clusters of FA with polar (L = H 2 O) and nonpolar ligands (L = Ar) have so far only been observed for the more stable t-FA rotamer.…”
Section: Introductionsupporting
confidence: 91%
“…The frequency positions of the S 0 -S 1 origins for A−D already provide some clue to the structures involved. The electronic origins of B−D are very red-shifted from that of tFA (36004 cm −1 ) and tAA (35902 cm −1 ), 27 while that for conformer A is shifted to the blue, as shown in Figure 3. Previous studies 28 have identified H 2 O complexes with tFA in which H 2 O acts either as a H-bond donor to the CO site or as a H-bond acceptor from the NH.…”
Section: Results and Analysismentioning
confidence: 89%
“…The amide group's conjugation with the phenyl ring produces a smaller than typical energy difference between trans-amide and cis-amide isomers, and in formanilide itself, both cis-and trans-isomers were observed in the expansion. 27 As a result, it was important also to explore this possibility in SAHA, where the cis-amide structure could potentially engage in hydrogen-bonding arrangements with the hydroxamic acid tail that are not available to trans-SAHA. However, the standard force field parameters in GAFF places an artificial barrier at the cis-amide configuration because in peptides, trans-amide structures are preferred over cis nearly exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, acetanilide (AA), as one kind of N-phenylamide, has been exclusively observed in a trans configuration in the gas phase recently [70]. The trans-AA has a C s symmetry structure in which all the heavy atoms are lying in the aromatic plane [71].…”
Section: Introductionmentioning
confidence: 99%